Soil bulk density and some related soil physical properties in relation to soil moisture content under New Hamdab conditions, northern Sudan - Ali Mustafa, Abbas; Mohammed Ahmed, Hisham Mousa (Gezira Journal of Agricultural Science, 2014)
This study was carried out during 2009/10, in New Hamdab Research Station Farm, Northern State, Sudan. Soil bulk density was determined with its corresponding soil moisture contents for depths 0-20 cm, 20-40 cm, 40-60 cm, 60-80 cm and 80-100 cm from a soil profile of 120 cm deep using the core method. Correlation between soil bulk density versus each of soil depths (D) and soil moisture contents were made, nevertheless, the bulk density related soil physical properties values in relation to moisture content were also estimated. The results indicated that soil bulk density had a significant linear positive relationship (P ≤ 0.001) with soil depth (r²=0.89), and negatively related to soil moisture content for all the tested depths(r²= 0.99, 0.98, 0.97, 0.58 and 0.98). The values of all related soil physical properties to soil bulk density increased with increasing gravimetric soil moisture content for all depths except for the air filled porosity which decreased. A calculated amount of irrigation water of 1693 m³/ha is needed to irrigate an air dry soil that contains about 5% moisture. أجريت هذه التجربة في موسم 2009/10 في مزرعة محطة بحوث الحامداب الجديدة، مشروع الحامداب الجديدة الزراعي في شمال السودان. تم تحديد الكثافة الظاهرية للتربة مع محتوي الماء عند أعماق 0- 20 سم ،20-40 سم ، 40-60 سم، 60-80 سم و 80- 100 سم من قطاع أرضى بعمق120سم مستخدمين طريقة Core method)). وقد تم إجراء اختبار لعلاقة الارتباط بين الكثافة الظاهرية للتربة و العمق، وكذلك بين الكثافة الظاهرية للتربة ومحتوي الماء. كما تم اختبار علاقة قيم خصائص التربة الفيزيائية ذات الصلة بالكثافة الظاهرية للتربة والمحتوي المائي. وقد أوضحت النتائج أن للكثافة الظاهرية للتربة علاقة معنوية ايجابية (p ≤ 0.001) مع عمق التربة (r² = 0.99)، وعلاقة معنوية عكسية مع محتوى الماء عند كل الأعماق أعلاه حيث كان معامل التحديد (Coefficient of determination) يساوى  0,99 ، 0,98، 0,97 و 0,57 على التوالي. ولذلك فمعادلات الانحدار كانت مناسبة لمنحنى الكثافة الظاهرية للتربة لكل الأعماق. كذلك ازدادت قيم كل خصائص التربة الفيزيائية ذات الصلة بالكثافة الظاهرية بزيادة محتوى الماء في التربة ماعدا مسامية هواء التربة والتي تناقصت بزيادة محتوى الماء في التربة. كما أبانت الدراسة أن كمية مياه الري المطلوبة لري هذه التربة عند درجة محتوى ماء 5% تساوى 1693 مترا مكعبا لكل هكتار وهذه الكمية التي تحتاجها هذه التربة عند الزراعة.